ANALISIS KINERJA MANAJEMEN PENGGUNAAN OBAT: EVALUASI PERESEPAN ANTIBIOTIK ISPA NON-PNEUMONIA DI PUSKESMAS INDONESIA (STUDI LITERATUR 2021–2025) - Tunggadewi, Aprillia Puspitasari; Putri Pratitis, Mera; Juanita Pakingki, Priska; Wisnu Wardana, Setiaji (Journal Pharma Saintika, 2025)
Non-pneumonia Acute Respiratory Infection (ARI) is a high-volume process area in Primary Health Care facilities (Puskesmas) and serves as a critical Key Performance Indicator (KPI) for antibiotic stewardship. This Systematic Literature Review (SLR) evaluates drug management performance across various Primary Health Care in Indonesia for the 2021-2025 period, utilizing data from 10 original research articles. The results indicate significant operational variance, with antibiotic usage rates ranging sharply from 4% to 65.2%. While several high-performing units have achieved the national efficiency target (≤20%), the majority exhibit weak prescriptive control, which escalates organizational risks related to Antimicrobial Resistance (AMR) and financial inefficiency. The first-line drug, Amoxicillin, dominates the formulary; however, a concerning regional trend toward the use of less efficient second-line agents (Cefadroxil) was detected. It is concluded that proactive managerial intervention is necessary, emphasizing the need for Pharmacists to conduct routine prospective prescription audits and strengthen inter-professional compliance to ensure resource optimization and clinical outcomes.